2021
DOI: 10.1186/s12859-021-03960-9
|View full text |Cite|
|
Sign up to set email alerts
|

DeepDist: real-value inter-residue distance prediction with deep residual convolutional network

Abstract: Background Driven by deep learning, inter-residue contact/distance prediction has been significantly improved and substantially enhanced ab initio protein structure prediction. Currently, most of the distance prediction methods classify inter-residue distances into multiple distance intervals instead of directly predicting real-value distances. The output of the former has to be converted into real-value distances to be used in tertiary structure prediction. Resul… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
57
0
3

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
2
1

Relationship

5
4

Authors

Journals

citations
Cited by 48 publications
(60 citation statements)
references
References 42 publications
0
57
0
3
Order By: Relevance
“…We applied a real-value distance predictor DeepDist [18] to predict an inter-residue distance map from the sequence of a protein target as matrix A ( L × L ), where L donates the sequence length and A [ i,j ] is the distance between residues i and j . A was compared with the distance matrix B ( L × L ) calculated from the coordinates of residues in a protein structure model to generate a difference map D .…”
Section: Methodsmentioning
confidence: 99%
“…We applied a real-value distance predictor DeepDist [18] to predict an inter-residue distance map from the sequence of a protein target as matrix A ( L × L ), where L donates the sequence length and A [ i,j ] is the distance between residues i and j . A was compared with the distance matrix B ( L × L ) calculated from the coordinates of residues in a protein structure model to generate a difference map D .…”
Section: Methodsmentioning
confidence: 99%
“…Recent studies ( Xu and Wang, 2019 ; Xu, 2019 ) have demonstrated the advantage of using distance maps in protein structure prediction over binary contacts as distances carry more physical constraint information of protein structures than contacts. The granularities of predicted distance maps vary from distance histograms to real-valued distances ( Greener et al, 2019 ; Adhikari, 2020 ; Ding and Gong, 2020 ; Li and Xu, 2020 ; Wu et al, 2021 ; Yang et al, 2020 ). Very recently, trRosetta ( Yang et al, 2020 ) has introduced inter-residue orientations in addition to distances to capture not only the spatial proximity information of the interacting pairs but also their relative angles and dihedrals.…”
Section: Granularities Of Protein Inter-residue Interaction Mapsmentioning
confidence: 99%
“…The computational methods for predicting protein tertiary structures and quaternary structures are periodically evaluated in the Critical Assessment of Protein Structure Prediction (CASP) (Kryshtafovych et al, 2014;Moult et al, 2016;Kryshtafovych et al, 2019;Kwon et al, 2021) and the Critical Assessment of Protein Interaction (CAPRI) (Lensink et al, 2016(Lensink et al, , 2018(Lensink et al, , 2021, respectively, or the joint experiment of the two. Driven by the application of deep learning methods to predicting residueresidue contacts and distances (Wang et al, 2017;Adhikari et al, 2018;Jones & Kandathil, 2018;Li et al, 2019;Hou et al, 2020;Senior et al, 2020;Yang et al, 2020;Wu et al, 2021) in the last several years, tertiary structure prediction has reached unprecedented high accuracy. In the 2020 CASP14 experiment, AlphaFold2 (Jumper et al, 2021) predicted high-quality structures for most CASP14 targets with the accuracy equal to or close to that of the experimental structure determination.…”
Section: Introductionmentioning
confidence: 99%